1995
DOI: 10.1007/bf00118595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of insecticide use on breeding birds in Christmas tree plantations in Quebec

Abstract: : This research, which was carried out in the spring of 1989 and 1990 in seven balsam fir (Abies balsamea) plantations in southeastern Quebec, examines potential deleterious effects of three insecticides (i.e. dimethoate, diazinon and insecticidal soap) on breeding American Robins (Turdus migratorius) (n=87 nests) and Song Sparrows (Melospizsa melodia) (n=41 nests). Through analyses of blood serum cholinesterases (AChE and BChE) activity both prior to and the second day following applications of the two organo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The American Robin, a relative of the clay-colored robin, is one of the species that has been most commonly affected. Rondeau and Desgranges (1995) found 48% ChE inhibition in blood serum of American robins from christmas tree plantations which had been sprayed with diazinon at 0.625 kg ai/ha. Also, ChE inhibition up to 72% was reported in the same species due to exposure to 2.2 kg ai/ha diazinon on ornamental trees (Decaire et al 1993).…”
Section: Discussionmentioning
confidence: 97%
“…The American Robin, a relative of the clay-colored robin, is one of the species that has been most commonly affected. Rondeau and Desgranges (1995) found 48% ChE inhibition in blood serum of American robins from christmas tree plantations which had been sprayed with diazinon at 0.625 kg ai/ha. Also, ChE inhibition up to 72% was reported in the same species due to exposure to 2.2 kg ai/ha diazinon on ornamental trees (Decaire et al 1993).…”
Section: Discussionmentioning
confidence: 97%
“…Robins have frequently been the focus of orchard pesticide studies, and significant effects have been Environmental Management (2014) 53:416-428 425 observed in this species (Cobb et al 2000;Fluetsch and Sparling 1994;Gill et al 2000;Graham and DesGranges 1993). However, Graham and DesGranges (1993) and Rondeau and DesGranges (1995) both reported significant plasma ChE depression in both chipping sparrows and robins in areas treated with OPs, but chipping sparrows were the only species to demonstrate significant brain ChE depression in Christmas tree plantations. The findings of these studies corroborate some of our results and contrast others.…”
Section: Discussionmentioning
confidence: 99%
“…However, little empirical data or guidance exists for choosing indicator species for contaminant studies with labile chemicals that have the potential for short-term but highly acute effects (Greig-Smith 1990). Indicator species used in field studies with pesticides are often selected on the basis of abundance and convenience in collecting data with that species (e.g., Millikin and Smith 1990; see also Bouvier et al 2005;Burgess et al 1999;Greig-Smith 1990;Jones 2003;Patnode and White 1991;Rondeau and DesGranges 1995). Selection of a species based on its abundance may provide greater numbers of individuals for study and analysis, but a species may be abundant because it is less sensitive or does not receive the exposure necessary to result in a toxic effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Putera and colleagues (1985) found that 89% of Mourning doves on eggs during a spray event (unspecified whether this was an insecticide or fungicide spray) failed whereas all nests with chicks were successful. Rondeau and Desgranges (1995) found that exposure to diazinon during laying or early incubation was particularly damaging. No adult toxicity was seen in the latter study; it was not looked for by Putera and colleagues. (c) Eggshell quality endpoints (Endpoints equivalent to: eggshell thickness, proportion of eggs cracked).…”
Section: Birdsmentioning
confidence: 97%